Ipsilateral Intravenous Catheter Placement in Breast Cancer Surgery Patients. (September 2021) - Naranjo, Julian; Portner, Erica R.; Jakub, James W.; Cheville, Andrea L.; Nuttall, Gregory A.
Abstract : BACKGROUND: There is a continued perception that intravenous line (IV) placement is contraindicated in the arm ipsilateral to prior breast cancer surgery to avoid breast cancer–related lymphedema (BCRL). The aim of this retrospective study was to determine the risk for development of BCRL in ipsilateral arm IV placement compared to contralateral arm IV placement to prior breast cancer surgery. METHODS: We performed a retrospective review, via our Integrated Clinical Systems and Epic Electronic Heath Record of IV placement for anesthesia and surgery in patients with a prior history of breast cancer surgery with or without axillary lymph node dissection. Complication rates were compared for IVs placed in the ipsilateral and contralateral arms. We identified 3724 patients undergoing 7896 IV placements between January 1, 2015, and May 5, 2018, with a prior history of breast cancer surgery via their index anesthesia and surgical procedures. RESULTS: The median time from breast cancer surgery to IV placement was 1.5 years (range, 1 day to 17.8 years). Of 2743 IVs placed in the arm contralateral to prior breast cancer surgery, 2 had a complication, corresponding to an incidence of 7.3 per 10, 000 (95% confidence interval [CI], 0.9–26.3 per 10, 000). Of 5153 IVs placed in the arm ipsilateral to prior breast cancer surgery, 2 IVs had a complication, for an incidence of 3.9 per 10, 000 (95% CI, 0.5–14.0 per 10, 000). The frequency of complications was not found to differ significantly between the groups ( P = .91), and the 95% CI for the risk difference (ipsilateral minus contralateral) was −23 to +8 complications per 10, 000. The complication rate is similar when only the first IV placed following breast cancer surgery is considered (overall 5.4 per 10, 000 [95% CI, 0.7–19.4] per 10, 000; contralateral 7.0 [95% CI, 0.2–39.0] per 10, 000, ipsilateral 4.4 [95% CI, 0.1–24.2] per 10, 000; P = 1.00; 95% CI for risk difference [ipsilateral minus contralateral], −41 to +22 per 10, 000). CONCLUSIONS: We found very few complications in patients who had an IV placed for surgery following a previous breast cancer surgery and no complications in those patients with IV placement ipsilateral with axillary node dissection. Avoidance of IV placement in the arm ipsilateral to breast cancer surgery is not necessary.